Denoising Deep Autoencoder Gaussian Mixture Model and Its Application for Robust Nonlinear Industrial Process Monitoring - Zhou, Yin-Chang; Li, Meng-Qian; Ji, Long-Bin (2021 International Conference on Computer Information Science and Artificial Intelligence (CISAI), 2021)
Process monitoring on high-dimensional nonlinear data is of great significance in the industrial process. This paper presents a denoising deep autoencoder Gaussian mixture model (DDAGMM) for anomaly detection in the industrial process. We add Gaussian white noise as preprocessing to the input data, which is further fed into a deep autoencoder to generate a low-dimensional representation and reconstruction error. Finally, we propose a monitoring strategy based on sample energy criterion to judge whether the new sample is anomaly or not. The DDAGMM can reduce the influence of outliers in the original data, has strong robustness, and can handle multi-modal data well. Compared with PCA, LDA and DAGMM based monitoring methods, the proposed counterpart shows superior performance.